Digitization of Documentation at the Scientific Archive of the National Institute of Archeology with Museum - Katrina Koleva; Kalina Sotirova; Elena Naidenova (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2016)
This paper is focused on the theory, standards and good practices in digitization of archival documents, as implemented in the Scientific Archive at the National Institute of Archeology with Museum (SA of NIAM-BAS). We explored metadata standards for archival documentation ISAD, EAD and “universal” cultural metadata standard Dublin Core trying to choose the best fit for representing of all the fields of SA of NIAM to de facto “standard”, used in NIAM-BAS since the 60 s . The archival documentation of archeological museum is very specific and contains five different types of documents: scientific report, field diary, field inventory book, photographic documentation and graphic documentation. The results and current annotation specifics are explained. Perspectives for future information system development are outlined.